Identity, Communication, and Conflict: An Experiment - Sumon K. Bhaumik; Subhasish M. Chowdhury; Ralitza Dimova; Hanna Fromell (Institute of Labor Economics (IZA), 2023)
We investigate experimentally the effects of information about native/immigrant identity, and the ability to communicate a self-chosen personal characteristic towards the rival on conflict behavior. In a two-player individual contest with British and Immigrant subjects in the UK we find that neither information about identity nor communicating self-characteristics significantly affect the average level of conflict. Both of those, however, significantly affect players' strategies, in the sense of the extent they involve conflict over time. Overall, the results indicate that inter-personal communication may help to mitigate high intensity conflicts when the identities are common knowledge among rivals.
Keywords: C72; C91; D72; 330; conflict; experiment; identity; immigrant; communication